Introduction to geographic information technology - Choudhury, Sujit; Chakrabati, Deepankar; Choudhury, Sujit (New Delhi I.K International publishing house Pvt. Ltd, 2009)
SECTION I GIT ; A CONCEPTUAL FRAMEWORK